2016
DOI: 10.1021/acsami.5b12284
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis and Characterization of Ge Embedded Electrospun Carbon Nanostructures as High Performance Anode Material for Lithium-Ion Batteries

Abstract: While active materials based on germanium (Ge) are considered as a promising alternative anodic electrode due to their relatively high reversible capacity and excellent lithium-ion diffusivity, the quite unstable structural/electrochemical stability and severe volume expansion or pulverization problems of Ge electrodes remain a considerable challenge in lithium ion batteries (LIBs). Here, we present the development of Ge embedded in one-dimensional carbon nanostructures (Ge/CNs) synthesized by the modified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 37 publications
1
35
1
Order By: Relevance
“…Li et al prepared Ge@CNF by electrospinning using Ge NPs DMF‐PAN solution as precursor solution. Then using CVD deposited carbon onto Ge@CNF to gain Ge@CNF@C. Lee et al reported Ge/CNFs synthesized by electrospinning using a mixed electrospun solution consisting of GeCl 4 precursor as an active material source and PAN as a carbon source. Wang et al proposed a simple and cheap method through electrospinning followed by atomic layer deposition (ALD) to fabricate Ge@graphene@TiO 2 core–shell NFs (Ge@G@TiO 2 NFs).…”
Section: Preparation Of Ge Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al prepared Ge@CNF by electrospinning using Ge NPs DMF‐PAN solution as precursor solution. Then using CVD deposited carbon onto Ge@CNF to gain Ge@CNF@C. Lee et al reported Ge/CNFs synthesized by electrospinning using a mixed electrospun solution consisting of GeCl 4 precursor as an active material source and PAN as a carbon source. Wang et al proposed a simple and cheap method through electrospinning followed by atomic layer deposition (ALD) to fabricate Ge@graphene@TiO 2 core–shell NFs (Ge@G@TiO 2 NFs).…”
Section: Preparation Of Ge Anodesmentioning
confidence: 99%
“…Besides, some special structure Ge–C compounds show an excellent electrochemistry performance, Ge–C 1D or 2D materials also show remarkable performance. Ge embedded in 1D carbon nanostructures (Ge/CNs) exhibited capacity retention of 85% at 200 mA g −1 . Carbon‐sheathed single crystalline Ge NWs produced by an SLS method showed a high reversible charge capacity of 963 mAh g −1 at a rate of 0.5 C after 100 cycles .…”
Section: Enhanced Electrochemical Performances Of Ge For Libsmentioning
confidence: 99%
“…With the reduced mass diffusion length along Sn QDs and enhanced electronic conductivity of N-doped CNFs, the Sn QDs@CNFs dis- played long cyclability of 887 mA h g −1 after 200 cycles at a cycling rate of 0.1 A g −1 . Germanium (Ge) is another promising anode material with a high theoretical capacity (1624 mA h g −1 for GeLi 4.4 ), higher Li-ion diffusion coefficient and electrical conductivity than Si [120]. Ge is applied to prepare electrospun anode materials for LIBs to overcome strain from volume change after lithiation.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…The gravimetric capacity (372 mAh g −1 ) of the commonly used graphite anodes is inadequate to meet the current requirements for energy storage systems. In the search for alternative anodes materials, the focus is mainly on transition metal oxides MO x , which store Li + ions through the conversion reaction MO x + 2 x Li + + 2 x e − ↔ M 0 + x Li 2 O, and IV group elements M 0 that are able to store larger amount of Li + ions through the alloying reaction M 0 + y Li + + y e − ↔ Li y M . Among the latter, germanium is the one endowed with by far superior properties (higher Li diffusivity and electronic conductivity, and smaller volume changes suffered during lithiation/delithiation process), which make it the most promising electrode material in spite of its smaller gravimetric capacity with respect to silicon (1624 against 4200 mAh g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the latest years, several studies have been conducted on electrode materials based on germanium and the cheaper germanium dioxide (GeO 2 ) . In GeO 2 , Li storage occurs via a conversion reaction leading to the irreversible formation of Li 2 O, which lowers down to 1126 mAh g −1 the gravimetric capacity attainable in the subsequent alloying reaction.…”
Section: Introductionmentioning
confidence: 99%